[BOOK REVIEW] POWER TO THE PEOPLE: HOW OPEN TECHNOLOGICAL INNOVATION IS ARMING TOMORROW’S TERRORISTS - Akhli, Rangga Amalul (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
Audrey Kurth Cronin, Power to the People: How Open Technological Innovation is Arming Tomorrow's Terrorists, Oxford University Press 2020, 440 Pages, 6-1/8 x 9-1/4 inches. ISBN: 9780190882143